(untitled) (Marketing Journal, 2025)
This article analyzes the role of innovative strategies in managing socio -economic development in the Olmazor district. The main goal of the study is to identify sustainable development pathways adapted to local conditions through digital technologies, pub lic participation, and effective resource management. The Analytic Hierarchy Process (AHP) method and panel data from 2010 to 2023 were used for evaluation. AHP helped assess various management strategies based on priority criteria, while panel data analys is revealed the long -term impacts of these strategies on socio -economic indicators. The findings indicate that digital transformation and public participation are among the most effective approaches. Sustainable resource management was also found to have l ong-term positive effects. The study shows that combining technological innovation with participatory governance can support effective local development. These insights can inform strategic planning in other urban areas with similar socio -economic contexts .